Pembiayaan Lembaga Keuangan Mikro Syariah dan Dampaknya Bagi Perkembangan Usaha Serta Peningkatan Kesejahteraan Usaha Mikro di Kota Serang - Neng Diah Syadiah; Rita Rosiana; Syihabudin Said (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this study was to examine the effect of financing by Islamic micro finance institutions on business development and improvement of micro business prosperity in Serang City, Banten. The research respondents were 45 micro enterpreneurs members of BMT Arta Bina, Serang City and obtained mudharabah financing. The data used are primary data in the form of questionnaires, analytical methods using linear regression with the help of SPSS 23.0 Software. Based on the results of the analysis and hypothesis testing, it can be concluded that mudharabah financing influences business development and improvement of micro business prosperity in Serang City.